Solve the equation:
(ax)ln(a)=(bx)ln(b)
ln(ax)ln(a)=ln(bx)ln(b)
ln(a) X ln(ax)=ln(b) X ln(bx)
ln(a)2+(lna X lnx) =ln(b)2+(lnb X lnx)
(lna X lnx)-(lnb X lnx)=ln(b)2+ln(a)2
lna(lnx)-lnb(lnx)=ln(b)2+ln(a)2
lna-lnb(lnx)=ln(b)2+ln(a)2
lnx=[ln(b)2+ln(a)2] / [lna-lnb]
x=e[ln(b)2+ln(a)2] / [lna-lnb]
I attempted to solve this equation, but I'm honestly not sure about my work. Could someone tell me if I have made a mistake somewhere?
(ax)ln(a)=(bx)ln(b)
ln(ax)ln(a)=ln(bx)ln(b)
ln(a) X ln(ax)=ln(b) X ln(bx)
ln(a)2+(lna X lnx) =ln(b)2+(lnb X lnx)
(lna X lnx)-(lnb X lnx)=ln(b)2+ln(a)2
lna(lnx)-lnb(lnx)=ln(b)2+ln(a)2
lna-lnb(lnx)=ln(b)2+ln(a)2
lnx=[ln(b)2+ln(a)2] / [lna-lnb]
x=e[ln(b)2+ln(a)2] / [lna-lnb]
I attempted to solve this equation, but I'm honestly not sure about my work. Could someone tell me if I have made a mistake somewhere?